2017
DOI: 10.1515/ttj-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Car Ownership Models in Iran: A Review of Methods and Determinants

Abstract: The achievement of sustainable transportation and the desire to reduce car ownership are important aspects of urban planning, especially in developing countries. This paper presents an overview of researches and studies conducted on car ownership to find the knowledge gap and neglected modelling methods that should be employed in the further researches in Iran as one of the Middle East countries. It is found that car ownership models have under gone modification and improvement from regression models towards d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…They called for caution in the application of the results because there exist other variables other than the ones employed in the study that can influence car ownership. Shaygan et al (2017) reviewed existing studies on car ownership models and determinants in Iran. They found that the accuracy of the existing regression and discrete choice models is hindered by reliable aggregate and disaggregate data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They called for caution in the application of the results because there exist other variables other than the ones employed in the study that can influence car ownership. Shaygan et al (2017) reviewed existing studies on car ownership models and determinants in Iran. They found that the accuracy of the existing regression and discrete choice models is hindered by reliable aggregate and disaggregate data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The data for vehicle in use in Iran show that the motorization and private car use rate is rapidly growing in Iran (OICA, 2015). The heavy trend of vehicle use is faster than most of the developed countries (Shaygan et al, 2017) with 15 percent of annual growth rate (Soltani, 2017). What makes this a threat is the coincidence of motorization growth with the lack of sufficient PT services (Mirmoghtadaee, 2016).…”
Section: Urban Transportation Context In Iranmentioning
confidence: 99%
“…Dash [1] et al proposed piecewise linear multinomial logit model to study the ownership of civil vehicles. Shaygan [2] et al conducted a comprehensive analysis on the vehicle ownership model in Iran. The research on the prediction of vehicle ownership in China started late, but many models and methods have been proposed, among which the prediction result of logistic model is ideal.…”
Section: Introductionmentioning
confidence: 99%